2023
DOI: 10.3390/pathogens12020344
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Methicillin-Resistant Staphylococci from the Dairy Value Chain in Two Indian States

Abstract: Bovine milk and milk products may contain pathogens, antimicrobial resistant bacteria, and antibiotic residues that could harm consumers. We analyzed 282 gram-positive isolates from milk samples from dairy farmers and vendors in Haryana and Assam, India, to assess the prevalence of methicillin-resistant staphylococci using microbiological tests, antibiotic susceptibility testing, and genotyping by PCR. The prevalence of genotypic methicillin resistance in isolates from raw milk samples was 5% [95% confidence i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 70 publications
2
3
0
Order By: Relevance
“…To our knowledge, no other study from India has reported β-lactamases in GNB isolated from pasteurized milk. This finding aligns with our previous report, which identified methicillin-resistant Gram-positive bacteria in pasteurized milk [50]. It could also be due to post-pasteurization contamination, potentially exacerbated by inadequate quality packaging and cold storage that encourages bacterial growth.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…To our knowledge, no other study from India has reported β-lactamases in GNB isolated from pasteurized milk. This finding aligns with our previous report, which identified methicillin-resistant Gram-positive bacteria in pasteurized milk [50]. It could also be due to post-pasteurization contamination, potentially exacerbated by inadequate quality packaging and cold storage that encourages bacterial growth.…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence of genotypic β-lactamases was 13% (CI (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)) in Haryana (a developed dairy sector) and 7% (CI (4-11)) in Assam (mainly informal dairy sector). These findings could indicate that intensive farms have a higher prevalence of antibiotic resistance genes, which has also been reported by others [48,49] and was similarly found in our previous study on Gram-positive bacteria in milk [50]. Even though we observed a higher prevalence of β-lactamase genes in milk isolates from Haryana compared to isolates from Assam, we discovered that milk isolates from Assam (77%, CI (70-82)) exhibited a higher phenotypic β-lactam resistance compared to isolates from Haryana (63%, CI (56-70)), and we therefore cannot conclude on the difference between the states.…”
Section: Discussionsupporting
confidence: 90%
“…Although, S. aureus with mecC genetic element in milk was first reported in India [35], we report the isolation of MRSA with mec C from rodents and shrews for the first time in India. The prevalence of MRSA in shrews and rodents in our study is 73.9% and 26.3% respectively.…”
Section: Discussionmentioning
confidence: 82%
“…Although, S. aureus with mecC genetic element in milk was first reported in India [ 37 ], we report the isolation of MRSA with mec C from rodents and shrews for the first time in India. The prevalence of MRSA in shrews and rodents in our study is 73.9% and 26.3% respectively.…”
Section: Discussionmentioning
confidence: 92%